CORRELATION OF IRON AND MYELOPEROXIDASE LEVELS IN ISCHEMIC HEART DISEASE - MUPPALA, THEJASWINI; RAJESH, DASARAJU; PATIL, PRIYA; V RAO, ASHALATHA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to estimate, compare, and correlate serum iron and myeloperoxidase (MPO) levels in acute ischemic heart disease (IHD) cases. Methods: Subjects for the study were divided into two groups of 35 acute IHD cases and 35 age and sex matched controls. Serum iron and MPO levels were assayed, and results compared. Statistical analysis: The comparison between two groups was done using the Student’s t-test. Correlation between iron and MPO was established using Pearson’s correlation test. Results: High serum MPO levels and low iron levels were observed in acute IHD cases in comparison to controls. There was no significant correlation between serum iron and MPO in acute IHD cases. Conclusion: High iron levels have a beneficial role, whereas high MPO levels have an inflammatory role in the development of IHD. Determination of serum iron and MPO levels in high-risk subjects may help in taking proper measures to prevent acute IHD.